A Note on Riemannian Supermanifolds (Bangladesh Journal of Scientific and Industrial Research, 2007)
The present research develops a theory of Riemannian supermanifolds up to a definition of Riemannian superspaces. Various fundamental concepts needed for the study of these spaces both from the Riemannian and the Lie theoretical viewpoints are introduced and some new notions of local forms of the torsion and curvature tensors are established for deriving certain constraints in classical case which is known as the super Bianchi identities. Bangladesh J. Sci. Ind. Res. 42(2), 121-134, 2007